Protective Effects of Cultivated Ginseng, Cultivated Wild Ginseng of Korean and Chinese Against CCl4 and t-BHP Induced Acute Hepatotoxicity in ICR Mice - Kim, Young-Jin; Park, Hee-Soo; Kwon, Ki-Rok; Kim, Ho-Hyun (Korean Pharmacopuncture Institute, 2007)
Objectives : This study was aimed at investigating live protection mechanism of Cultivated Ginseng and Cultivated Wild Ginseng of Korean and Chinese by inducing liver toxicity through and t-BHP in mice and evaluated serological findings. Methods : Experiment groups was categorized into untreated normal group, treated control group, and orally administered Cultivated Ginseng and Cultivated Wild Ginseng of Korean and Chinese experimental groups. At the termination of experiment, gross examination of the liver as well as Total bilirubin, AST, and ALT contents in the serum were evaluated. Results : 1. In the induced acute hepatotoxicity test, total bilirubin, AST and ALT didn't show significant differences between the control and experimental groups. 2. In the t-BHP induced acute hepatotoxicity test, total bilirubin, AST and ALT didn't show significant differences between the control and experimental groups. Conclusion : Taken together, Cultivated Ginseng and Cultivated Wild Ginseng of Korean and Chinese cannot be effectively used for recovering the liver functions in acute hepatotoxicity tests using and t-BHP. Further researches, for example treated long period, must be tried to verify the efficacies.